Implementation of Telemedicine in Medical Practice: Management and Theoretical-Legal Aspects - Anishchenko, M. A.; Prasov, O. O.; Krasnokutskyi, O. V.; Glazunov, V. V.; Myrnyi, S. P.; Аніщенко, Михайло Анатолійович; Мирний, Сергій Петрович (My University, 2024)
The development of medicine has a positive impact on the provision of services in the medical field, since science and technology in a global sense are not static and continue to advance, their effectiveness depends on the regulatory consolidation and actions of governing bodies. Issues regarding the implementation of telemedicine in Ukraine are relevant and important, as due to military actions, not every person can bodily visit a doctor. The implementation of a remote form and provision of services to patients in an online format makes it possible to avoid the spread of epidemics, which also has a positive effect on the prevention of the diseases spread. The relevance is expressed in the effective actions of governing bodies to solve modern important problematic issues, as the implementation of telemedicine can solve the problematic aspects that doctors and patients face today. People have the right to receive medical services effectively and they should always be available, if online consultation can save life and health, it should be implemented and applied in practice. The purpose is theoretical analysis of the implementation of telemedicine in medical practice and disclosure of management and legal aspects. The object is the normative framework that regulates the issue of telemedicine in medical practice. While analyzing and studying this issue, legal and general scientific methods were used. A detailed theoretical and legal analysis of the implementation of telemedicine in medical practice makes it possible to identify problematic issues and shortcomings in the legislative base and management of the medical sphere in our country and to propose ways to solve them. Key problems in the medical field need to be reformed widely and globally, taking into account all the risks of modernity. This will make it possible to solve the issue of the availability of medical services for patients who cannot visit a doctor in Ukraine due to hostilities, which will now make it possible to solve the urgent problems of our time. International norms are the foundation for upholding the rights of patients and our country must definitely take them into account when engaging in legislative activities. The implementation of telemedicine into medical practice will make it possible to prevent diseases and epidemics, and also help to avoid the spread of the COVID-19 pandemic not only in Ukraine, but also in the world. Having analyzed the theoretical and legal basis, the scientific views of scholars, we came to the conclusion that computerization, digitalization, remote consultations have a positive effect not only on the medical, but also on the legal sphere. This simplifies the work of notaries and makes it more efficient when conducting legal transactions and allows to avoid judicial appeals in cases regarding their invalidity, as notaries could independently verify the legal capacity of persons with their consent through telemedicine. We believe that this opinion should be further researched and implemented in practice, taking into account all the gaps and problematic aspects.
Keywords: Computerization; Digitalization; Doctor; Legislation; Management; Medical Practice; Online; Patient; Regulatory and legal basis; Remote consultations; Telemedicine; medical reform; Theoretical and legal basis